Governance and success in U.S. equity crowdfunding - Douglas J. Cumming; Sofia Atiqah Johan; Robert S. Reardon (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
We propose three governance mechanisms pertinent to equity crowdfunding and campaign success through mitigating pronounced information asymmetries and agency problems. First, unlike IPOs for which the effect of Delaware incorporation has declined or disappeared over time, we propose Delaware incorporation matters a great deal for success in the new setting of equity crowdfunding. Second, we propose that security design is a critical tool for equity crowdfunding success and even more important than the limited 2-year financial statement disclosure. Third, we propose that platforms as intermediaries between entrepreneurs and investors play an important role in mitigating and sometimes exacerbating information asymmetries and agency problems. The population of equity crowdfunding campaigns from market inception in May 2016 to Q2, 2021 in the United States provides strong support for these propositions.
Keywords: G21; G28; G51; 330; Equity Crowdfunding; Governance; Delaware Incorporation; Fintech; COVID-19